PENGARUH CONTENT MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK LIP TINT BARENBLISS - Hayati, Nur; Sudarwanto, Tri (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This study aims to analyze the influence of content marketing and brand image on the purchase decision of Peach Makes Perfect lip tint Barenbliss products. Primary data was obtained through a survey using a questionnaire to 384 respondents who are followers of Barenbliss's social media. Data analysis was carried out with a descriptive quantitative approach using the multiple linear regression method. The results of the study show that content marketing and brand image simultaneously have a significant effect on the purchase decision of Peach Makes Perfect lip tint Barenbliss products. The practical implication of this research is the importance of companies in paying attention to attractive content marketing strategies in order to be able to create a good brand image to be able to influence consumer purchase decisions. This research is expected to contribute to understanding consumer behavior in the digital era and become a reference for companies in designing effective marketing strategies.